The Transition of Limited Face-to-Face Learning After Covid-19 Pandemic at Islamic Private Junior High Schools Pontianak - Husni Syahrudin; Iwan Ramadhan; Nur Meily Adlika; Muhammad Agus Hardiansyah; Yudhistira Oscar Olendo; Fitria Arifiyanti (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
The article aimed to analyze the limited face-to-face learning strategy during the Covid-19 pandemic at Islamic Private Junior High Schools Pontianak. With the limited implementation of face-to-face learning, schools were required to design learning strategies that in accordance with the conditions of learning implementation during the Covid-19 pandemic. As has been applied at this school from the results of this study, both in the school environment, teaching and learning activities and the availability of various health protocol facilities as a strategy for implementing face-to-face learning during the pandemic. The research used descriptive qualitative with data collection techniques incuded observation, interviews and documentation. The limitations of face-to-face learning at Islamic Private Junior High Schools Pontianak were the number of years of study at school, the lack of interaction and the implementation of assessments which had better transformation. Meanwhile, Islamic Private Junior High Schools Pontianak had merely once a week for learning implementation, so schools must maximize learning strategies. Keywords: Limited Face-to-Face Learning, Learning After Covid 19, Transition Learning Online